Principios de eficiencia y eficacia en el acto administrativo que declara la urgencia manifiesta por la emergencia económica y sanitaria que produjo el covid 19 en el departamento del Atlántico (2022)
The main purpose of this work is to determine the shortcomings that manifest urgency contracts present in state contracting, the constant abuse of the figure to evade the bidding processes, evading the controls that leave in suspense the main bases from public administration. The haste in the adjudication of manifest emergency processes means that strict controls are not taken under this selection mechanism, the inefficient motivation of the administrative acts that declare manifest urgency, cause the figure to be distorted, in many cases evading adequate satisfaction of the general interest, which must be devoid of any contract. Taking into account the nature of this contract in which a bidding process is not necessary, it becomes a mechanism of predilection for the corrupt who directly grant the contract in exchange for perks and other bureaucratic favors. It is in our interest to find mechanisms that allow the evaluation of the degrees of satisfaction, in our case measuring the parameters of efficiency and effectiveness of the contract of manifest urgency is a tool that measures the degree of benefit of the satisfaction of the public service and general interest.